CORRELATIONS BETWEEN ATTITUDES AND RATIONAL USE OF ANTACID IN SELF MEDICATION (Study on Health Students of Universitas Muhammadiyyah Malang) - Husniar, Witri Rochaeni; Pristianty, Liza; Hidayati, Ika Ratna (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Intoduction: Self-medication is the selection and use of modern drugs, herbs, and traditional medicines by individuals to overcome diseases or symptoms of disease. One mild disease that can be treated with self-medication is gastritis. The over-the-counter medication which is frequently used in treating gastritis in self- medication is antacid.Objective: To determine the correlation between attitudes and antacid rational use in self-medication among health students at the Universitas Muhammadiyah Malang.Methods:  observational analytic method using questionnaire was used for this study. The sample consist of 97 people who met inclusion criteria. Sampling was done by purposive sampling method, then the data were analyzed using Rank Spearman analysis using SPSS. This research was conducted at the campus II, Universitas Muhammadiyah Malang.Results: The results showed that 97 students of health had negative attitudes of 42% (41) and positive attitude of 58 % (56). The rational use of antacid drugs as much as 60% (58), the irrational use of drugs is 40% (39). Results of analysis using Spearman rank correlation test values were rcount 0.680 > rtable 0.202.Conclusion: The results of this study indicated that there is a significant correlation between a positive attitude to the antacid rational use in self-medication on Health Students of Universitas Muhammadiyah Malang